Phenotypic characterization of breast cancer: the role of CDC42 - Chrysanthou, Eleni; Gorringe, Kylie L.; Joseph, Chitra; Craze, Madeleine L.; Nolan, Christopher C.; Diez-Rodriguez, Maria; Green, Andrew R.; Rakha, Emad A.; Ellis, Ian O.; Mukherjee, Abhik (Springer, 2017)
Purpose: The molecular landscape of breast cancer (BC), especially of the Luminal A subtype, remains to be fully delineated. Transcriptomic data shows that Luminal A tumours are enriched for aberrant expression of genes in the cell division control 42 homolog (CDC42) pathway. This study aims to investigate protein expression of CDC42 in BC and assess its clinicopathological significance. Methods: Expression of CDC42 protein was examined by immunohistochemistry on tissue microarrays in a well characterised cohort of 895 early stage (I-IIIa) primary invasive BCs. Results: CDC42 expression was observed in both the cytoplasm and nucleus of BC cells. High nuclear CDC42 expression demonstrated a significant correlation with ER positive, low-grade tumours and was more common in the lobular histological subtype (all p<0.001). In contrast, cytoplasmic CDC42 showed increased expression in the ductal subtype (p<0.001) and correlated with negative prognostic features such as larger size, higher grade (p<0.05), and higher Ki67 labelling index (p=0.001). Nuclear CDC42 expression was associated with a longer BC specific survival in all cases (p=0.025) and in luminal ER positive tumours (p=0.011). In multivariate analyses including size, grade, lymph node stage and intrinsic subtype, CDC42 was an independent prognostic factor (p=0.032). Conclusion: The results indicate that CDC42 is important molecule in luminal BC, with prognostic significance.